A theological analysis of the healing movement revival in Indonesia - Jefri Hina Remi Katu (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2023)
Pentecostal and healing practices could not be separated in Pentecostal Theology because healing practices are the most phenomenal practice in the Pentecostal tradition.Â This practice is essential regarding the phenomenal growth of Pentecostal Churches worldwide.Â Especially in the context of Pentecostal churches in Indonesia, I will describe how the Pentecostal churches grew so fast that the healing revival impacted them.Â I will give my analytical critics of this phenomenon through the discussion with the works of literature available and bring my suggestion and contribution to Pentecostal Theology regarding the vital doctrine of Pentecostal, which is the healing practices.